Engineering HER2-targeted biparatopic antibodies to promote receptor internalization and restore antitumor efficacy - Liu, Xinlin; Yu, Wanpeng; Wang, Yihuan; Xing, Dongming; Huang, Haiming; Zhu, Wenjing; Sun, Peng (Frontiers in Immunology, 2025)
HER2 is a well-established oncogenic driver in breast, gastric, and other solid tumors. While HER2-targeted therapies such as trastuzumab and pertuzumab have improved clinical outcomes, resistance, particularly to trastuzumab, remains a major therapeutic challenge. Here, we engineered two IgG-VHH biparatopic antibodies (bpAbs), A9B5-Bs-5 and A9B5-Bs-7, incorporating an ECD I-binding nanobody A9B5 with the IgG scaffolds. These bpAbs target non-overlapping epitopes on the HER2 extracellular domain, promoting rapid receptor internalization and demonstrating superior antitumor activity compared to the trastuzumab and pertuzumab combination in trastuzumab-resistant tumor cells. Structural modeling suggests that both bpAbs engage HER2 in a trans-binding mode, leading to receptor clustering and interference with ligand-driven HER2 heterodimerization. These findings demonstrate that epitope-guided biparatopic antibody design can enhance HER2 downregulation and restore sensitivity to HER2-targeted therapy in vitro, providing a strategy for the development of next-generation receptor-targeted biologics.